Perkembangan Masa Remaja - Siti Fatimah Mustari; Anisa Purnama Sari; Linda Yarni (Universitas 45 Surabaya, 2024)
This research explores and evaluates task, physical, intellectual, emotional development. Puberty or puberty is a period in a person’s life where significant physical, emotional and social changes occur in preparation for adulthood. Puberty is also a time when individuals begin to understand their gender roles in society and experience significant social changes. Researchers make use of magazines and websites related to the title being studied in addition to books. A qualitative approach based on observable events and scientific reasoning is also used by researchers. The rapid growth and development that occurs during puberty is partly dependent on hereditary factors, which affect the endocrine glands, and poor nutrition in childhood causes reduced production of growth hormone. Emotional disturbances can affect growth because they result in excessive production of detrimental adrenal steroids. Growth hormone.